The Arab League and the Western Sahara Conflict: The politics of a sheer neglect - Iratni, Belkacem (Africana Studia, 2020)
The Arab League has paid little attention to the issue of Western Sahara. This neglect was supposedly due to the concern of this league to ensure the solidarity among its member States and avoid a further fragmentation of the Arab World. This League did not favour the right of the Saharawi people for Self-determination and has provided a firm support to the autonomy plan which Morocco has tried to complete in the areas of the Western Sahara brought under its control after the demise of Spain to fulfill its mandate duties, which included the decolonization of this territory. Individually, the positions of the member States have varied – according to their ideological beliefs, geostrategic interests and political alignments – between those supporting the Saharawi cause and those backing up the integration of the Western Sahara to Morocco,. The attitude of the Arab League towards the Western Sahara conflict may evolve with the changes that are occurring in the home policy of its member States. The more the Arab societies advance in the process of democratization, the more the Arab League will move to respect international legality and promote the rights of the peoples. Keywords: The League of the Arab States, Western Sahara conflict, decolonization.